Industrial Aplication of Catalytic Systems for n-Heptane Isomerization - Laura Olivia Alemán-Vázquez; José Luis Cano-Domínguez; José Roberto Villagómez-Ibarra; Enelio Torres-García (Molecules, 2011)
The ideal gasoline must have a high pump octane number, in the 86 to 94 range, and a low environmental impact. Alkanes, as a family, have much lower photochemical reactivities than aromatics or olefins, but only the highly branched alkanes have adequate octane numbers. The purpose of this work is to examine the possibilities of extending the technological alternative of paraffin isomerization to heavier feedstocks (i.e., n-heptane) using non-conventional catalytic systems which have been previously proposed in the literature: a Pt/sulfated zirconia catalyst and a molybdenum sub-oxide catalyst. Under the experimental conditions at which these catalysts have been evaluated, the molybdenum sub-oxide catalyst maintains a good activity and selectivity to isomerization after 24 h, while the Pt/sulfated zirconia catalyst shows a higher dimethylpentanes/methylhexanes ratio, probably due to a lower operating temperature, but also a high formation of cracking products, and presents signs of deactivation after 8 h. Though much remains to be done, the performance of these catalysts indicates that there are good perspectives for their industrial application in the isomerization of n-heptane and heavier alkanes.